Embarazo en adolescentes escolarizadas como problema de salud pública (2021)
In contrast to the priority given to early pregnancy as a social problem and the development of a diversified normative and doctrinal body, there have been few results and derived impacts: It is a growing situation in Colombia. In the field of educational policy, it is considered pertinent to strengthen a training process in Sex Education as a way to face this situation. Consequently, the present research work aims to analyze the pregnancy of adolescents enrolled in school, understanding this circumstance as a public health problem. A mixed research strategy was applied in which documents related to the policy of Sexual Education were analyzed, and the perception and opinion of key actors in the situation was collected (semi-structured interviews to students mothers, questionnaires with Likert-type responses to Parents/Representants, Teachers, Educational Directors, Health Personnel). A complex situation is located in which adolescent mothers –although they remain in the school system- go on to a life marked by motherhood. Likewise, discrepant positions are observed between Teachers, Educational Directors and Health Personnel, with respect to the legal and doctrinal documents of what Sexual Education should be. It is concluded that - in addition to the inclusion of a public health approach - it is necessary in the training processes to develop organizational and managerial reforms as a basis for the integration of sexuality education into the curriculum as a transversal program.